1976
DOI: 10.1177/074171367602600302
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Education for Non-Practicing Professionals: a Case Study of a Program for Pharmacists

Abstract: This study deals with the development and evaluation of a continuing education course designed specifically for temporarily non-practicing pharmacists. The course consisted of a one-hour audio cassette tape and a printed supplement covering materials based on needs expressed by non-practicing pharmacists in a previous study. This study shows that non-practicing pharmacists tend to become isolated from their profession, fail to participate in formal and informal methods of continuing education, and are apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…Thus, the courses were equally of value to all practitioners. This overall satisfaction was similar to previous studies in which pharmacists found specific individual courses to be of value (2,8,9). The respondents indicated a degree of uncertainty that the majority of the material presented in the course was new to them.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the courses were equally of value to all practitioners. This overall satisfaction was similar to previous studies in which pharmacists found specific individual courses to be of value (2,8,9). The respondents indicated a degree of uncertainty that the majority of the material presented in the course was new to them.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have shown similar findings (8,9). These audio cassette courses represent only one of a variety of types of learning experiences which are available to pharmacists.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…ithin the past decade recipients of funds W for continuing education programs have been encouraged to incorporate an evaluation 0 1981 by The Regents of the University of California 0272-3425/82/0110005 + 08/300.50 component in their program designs. Although the literature is replete with evaluation studies of educational programs, generally, these reports are limited to studies of learners in traditional educational settings, e.g., confined or employed by an organization (2,3), in the military service (4) or enrolled in a single course over time ( 5 , 6). Evaluation methods based upon behavioral change, for example, seem better suited for traditional situations, given interest, time and funds.…”
mentioning
confidence: 99%